Vertically-Integrated Photonic Devices in Silicon-on-Insulator - Brooks, Christopher (My University, 2010)
The functional density of photonic integrated circuits can be significantly increased by stacking multiple waveguide layers. These vertically-integrated devices require optical couplers to switch light signals between their layers. In this thesis, optical coupling between two stacked silicon-on-insulator slab waveguides has been demonstrated with a coupling efficiency of 68±4%, obtained with a coupler length of 3535 μm. The main advantage of using a silicon-based material system for photonic integrated circuits is its compatability with existing electronics manufacturing processes, facilitating cost-effective fabrication and the monolithic integration of both photonics and electronics on a single device.
Coupling between more complex silicon-on-insulator waveguide structures with lateral confinement was then demonstrated. The coupling ratio between stacked silicon rib wavelengths was measured to be 54±4%, while ratios of 71±4% and 93±4% were obtained for stacked channel waveguide and multimode interferometer-based couplers respectively. The corresponding coupler lengths for these three designs were 572 μm, 690 μm and 241 μm respectively. The sensitivity of these couplers to the input wavelength and polarization state has also been evaluated. These vertical-integrated couplers, along with other structures, have been thoroughly simulated, including their tolerance to fabrication errors. Novel fabrication processes used to demonstrate coupling in proof-of-concept devices have been developed, including an in-house wafer bonding procedure.
Pages viii, xii, xiv, 32, 110, 182, 188, 194 were blank and therefore omitted.
Keywords: engineering physics; vertically-integrated photonic devices; silicon-on-insulator